2023
DOI: 10.30841/2708-8731.6.2023.289993
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of diagnostic and treatment measures for chronic pelvic pain in women in routine clinical practice

S.O. Shurpyak,
I.V. Kozlovskyi,
V.I. Pyrohova
et al.

Abstract: Chronic pelvic pain (CPP) for a long time remains one of the important medical and social problems due to the variability of clinical manifestations, negative impact on reproductive health and quality of patient’s life. Epidemiological studies indicate that CPP occurs in 15-20% of women of reproductive age. According to many authors, diagnosis and treatment of CPP is not an easy task due to unclear diagnostic criteria, variety of symptoms, insufficient diagnostic tools, etc.The objective: to analyze the diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Endometriosis presents with characteristic symptoms such as dysmenorrhea, infertility, deep dyspareunia, chronic fatigue, chronic pelvic pain and ovulation pain. Epidemiological studies indicate that chronic pelvic pain is diagnosed in 15-20% of women of reproductive age [4][5][6]. Adenomyosis is often combined with endometriosis and is a similar disease [7,8].…”
Section: психосоматичний стан жінок репродуктивного віку з аденоміозо...mentioning
confidence: 99%
See 2 more Smart Citations
“…Endometriosis presents with characteristic symptoms such as dysmenorrhea, infertility, deep dyspareunia, chronic fatigue, chronic pelvic pain and ovulation pain. Epidemiological studies indicate that chronic pelvic pain is diagnosed in 15-20% of women of reproductive age [4][5][6]. Adenomyosis is often combined with endometriosis and is a similar disease [7,8].…”
Section: психосоматичний стан жінок репродуктивного віку з аденоміозо...mentioning
confidence: 99%
“…However, it is should be taking into account that sometimes pelvic pain is not caused by adenomyosis. S. Shurpyak et al (2023), analyzed the diagnostic and therapeutic measures in the presence of pelvic pain syndrome in women in routine clinical practice, because chronic pelvic pain for a long time remains one of the important medical and social problems. They revealed that in more than half of the analyzed cases (51.5%), the reason for the referral of women for the purpose of examination is not a pelvic pain syndrome, but a pathology that could be related to or be a consequence of diseases that lead to the development of pelvic pain (abnormal uterine bleeding, infertility, etc.)…”
Section: Table 5 History Of Gynecological Diseases In Patients With A...mentioning
confidence: 99%
See 1 more Smart Citation